An educational study on the effect of energy consumption on capital productivity in the agricultural sector by the ARDL method (an Iran case study) - Keshavarziyan, Maryam (2020)
This paper investigates the effects of energy consumption on capital productivity using transom production in the agricultural sector in Iran through an appropriate econometric method, and autoregressive distributed lag (ARDL). The method of this research is descriptive and using methods related to the objectives. The findings show that the per capita energy consumption ratio in the long-term relationship is -3.8, it means that the capital productivity decrease about 4% for one percent increase in per capita energy consumption. In this study, the factors affecting energy productivity have been studied in the agricultural sector during 1990-2016 in Iran. In this regard, energy productivity was first calculated using a partial productivity indicator. The results revealed that energy productivity in the agricultural sector increased by average 1.1% per year during the study period. The average of labor force per unit of capital and the average human capital per unit of capital is Affectless on the capital productivity, so the average energy consumption per unit of capital   effect on capital productivity.